Assessment of Izalpinin Inhibitory Effect on Diabetes via Molecular Docking Method - Thanh Tung, Bui; Thuy Tien, Nguyen; Tuan Minh, Nguyen; Minh Trang, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 42 No 2, 2026)
Diabetes mellitus is a common non-communicable disease globally and one of the leading causes of death due to cardiovascular diseases compared to other causes. Izalpinin is a flavonoid compound found in several medicinal plants with potential antidiabetic effects. This study evaluates the inhibitory effects of Izalpinin on three targets (α-glucosidase, Aldose reductase, Dipeptidyl-peptidase IV) involved in the pathogenesis of diabetes using molecular docking methods. The 3D structures of the targets were obtained from the RCSB Protein Data Bank. The structure of Izalpinin was retrieved from the PubChem database. Molecular docking screening was performed using AutoDock Vina. Lipinski's Rule of Five was applied to assess the drug-like properties of Izalpinin. The pharmacokinetic parameters of Izalpinin were evaluated using the pkCSM tool. Oral bioavailability was assessed using the SwissADME tool. The results showed that Izalpinin had a significantly low binding energy with Aldose reductase (∆G = −10.3 kcal/mol). Lipinski analysis indicated that Izalpinin possesses drug-like properties. Predicted pharmacokinetic parameters showed that the compound has good absorption and low toxicity. However, Izalpinin does not meet the criteria for oral bioavailability. Therefore, further studies are needed to develop this compound as a potential diabetes treatment.